Widespread presence of potato virus Y in the main potato-producing region of Paraguay - Diana C. Zorrilla; Marcelo Alborno-Jover; Yerutí Mongelos-Franco; Blanca Coronel; Heron Kraide; Lino Ramirez-Ayala; Adans Colman; Jorge A. M. Rezende; Elliot W. Kitajima; Alfredo Gryciuk Almeida; Arnaldo Esquivel-Fariña (Journal of Plant Pathology, 2025)

Comparative lifespan and healthspan of nonhuman primate species common to biomedical research - Hillary F. Huber; Hannah C. Ainsworth; Ellen E. Quillen; Adam Salmon; Corinna Ross; Adinda D. Azhar; Karen Bales; Michele A. Basso; Kristine Coleman; Ricki Colman; Huda S. Darusman; William Hopkins; et al. (GeroScience, 2024)

Adaptation of sea turtles to climate warming: Will phenological responses be sufficient to counteract changes in reproductive output? - M. M. P. B. Fuentes; A. J. B. Santos; A. Abreu‐Grobois; R. Briseño‐Dueñas; J. Al‐Khayat; S. Hamza; S. Saliba; D. Anderson; K. W. Rusenko; N. J. Mitchell; M. Gammon; B. P. Bentley; et al. (Global Change Biology, 2024)
Sea turtles are vulnerable to climate change since their reproductive output is influenced by incubating temperatures, with warmer temperatures causing lower hatching success and increased feminization of embryos. Their ability to cope with projected increases in ambient temperatures will depend on their capacity to adapt to shifts in climatic regimes. Here, we assessed the extent to which phenological shifts could mitigate impacts from increases in ambient temperatures (from 1.5 to 3°C in air temperatures and from 1.4 to 2.3°C in sea surface temperatures by 2100 at our sites) on four species of sea turtles, under a “middle of the road” scenario (SSP2‐4.5). Sand temperatures at sea turtle nesting sites are projected to increase from 0.58 to 4.17°C by 2100 and expected shifts in nesting of 26–43 days earlier will not be sufficient to maintain current incubation temperatures at 7 (29%) of our sites, hatching success rates at 10 (42%) of our sites, with current trends in hatchling sex ratio being able to be maintained at half of the sites. We also calculated the phenological shifts that would be required (both backward for an earlier shift in nesting and forward for a later shift) to keep up with present‐day incubation temperatures, hatching success rates, and sex ratios. The required shifts backward in nesting for incubation temperatures ranged from −20 to −191 days, whereas the required shifts forward ranged from +54 to +180 days. However, for half of the sites, no matter the shift the median incubation temperature will always be warmer than the 75th percentile of current ranges. Given that phenological shifts will not be able to ameliorate predicted changes in temperature, hatching success and sex ratio at most sites, turtles may need to use other adaptive responses and/or there is the need to enhance sea turtle resilience to climate warming.

The dynamic influence of subsurface geological processes on the assembly and diversification of thermophilic microbial communities in continental hydrothermal systems - Kenneth W.W. Sims; Cole M. Messa; Sean R. Scott; Andrew D. Parsekian; Andrew Miller; Abraham L. Role; Timothy P. Moloney; Everett L. Shock; Jacob B. Lowenstern; R. Blaine McCleskey; Matthew A. Charette; Bradley J. Carr; et al. (Geochimica et Cosmochimica Acta, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Direct and indirect seasonal rainfall forecasts for East Africa using global dynamical models - Andrew W. Colman; Richard J. Graham; Michael K. Davey (International Journal of Climatology, 2020)
Regional‐scale seasonal climate outlooks are typically produced using forecast information either local to the region or from another area with teleconnections to the region. Dynamical global long‐range forecast (LRF) systems can provide both types of information, and these two approaches are compared in the context of seasonal rainfall forecasts for two adjoining areas in the Greater Horn of Africa region in tropical East Africa. The direct method utilizes the unprocessed LRF outputs for the region. For the “indirect” method, canonical correlation analysis is used and works by identifying patterns in historical LRF predictions over large tropical domains that relate to observed variability in the East Africa regions. For a given year, projections of the LRF forecasts onto those patterns can then be employed to construct the regional forecasts. This approach takes advantage of the tendency for LRF systems to have greater skill for large‐scale variability than for smaller regional‐scale features. Using case studies, it is found the two approaches contain complementary information: the indirect approach can provide notable skill benefits in years with strong large‐scale forcing while in some years, particularly when large‐scale signals are weak, the “direct” forecast are superior. Skill comparisons over many years found that, although results are region/season dependent, in general the indirect approach has higher skill overall—with improvements equal to or greater than those afforded by a 1‐month reduction in lead time with the direct approach. Results for both methods used separately and in combination are provided for the March–April–May and September‐to‐December seasons in the two regions, using data from currently operational dynamical LRF systems. Skill was best for the September‐to‐December season in the southern region, using “indirect” forecasts. The “direct” approach was better than “indirect” for the March‐to‐May season in the northern region. In general, combination did not produce a substantial benefit.

A Marine Isotope Stage 4 age for Pleistocene raised beach deposits near Fethard, southern Ireland - Colman Gallagher; Matt W. Telfer; Colm Ó Cofaigh (Journal of Quaternary Science, 2015)
Raised beach deposits around the Irish coast have been interpreted as interglacial or last glacial in age. On the south coast of Ireland, the Courtmacsherry Formation raised beach (CFB), near Fethard, County Wexford, was dated using optically stimulated luminescence (OSL). This site was previously dated to Marine Isotope Stage (MIS) 6–5, but more recent dating of the CFB elsewhere along the south coast shows it is considerably younger (MIS 4–3). The OSL analyses in this paper aimed to determine if new dating would support the greater age of the Fethard raised beach or realign it with the CFB. The new OSL ages place the formation of the Fethard raised beach between 57 ± 6 and 45 ± 6 ka, with 53 ± 5 ka the most likely age if a single depositional event is assumed. This is consistent with OSL dates of the CFB elsewhere. An MIS 4–3 age has important implications in understanding the palaeogeography and timing of glaciation in Ireland, and requires a reassessment of regional relative sea level history. As the eustatic response to global ice volume resulted in lowered relative sea level during MIS 4–2, a crustal response to glaciation is implied by the new dates.

On the contribution of local feedback mechanisms to the range of climate sensitivity in two GCM ensembles - M. J. Webb; C. A. Senior; D. M. H. Sexton; W. J. Ingram; K. D. Williams; M. A. Ringer; B. J. McAvaney; R. Colman; B. J. Soden; R. Gudgel; T. Knutson; S. Emori; et al. (Climate Dynamics, 2006)

Chronology of Sediment Deposition in Upper Klamath Lake, Oregon - Steven M. Colman; J. Platt Bradbury; John P. McGeehin; Charles W. Holmes; David Edginton; Andrei M. Sarna-Wojcicki (Journal of Paleolimnology, 2004)

Record of Late Pleistocene Glaciation and Deglaciation in the Southern Cascade Range. I. Petrological Evidence from Lacustrine Sediment in Upper Klamath Lake, Southern Oregon - Richard L. Reynolds; Joseph G. Rosenbaum; Josh Rapp; Michael W. Kerwin; J. Platt Bradbury; Steven Colman; David Adam (Journal of Paleolimnology, 2004)

Statistical prediction of global sea‐surface temperature anomalies - A. W. Colman; M. K. Davey (International Journal of Climatology, 2003)
Sea‐surface temperature (SST) is one of the principal factors that influence seasonal climate variability, and most seasonal prediction schemes make use of information regarding SST anomalies. In particular, dynamical atmospheric prediction models require global gridded SST data prescribed through the target season. The simplest way of providing those data is to persist the SST anomalies observed at the start of the forecast at each grid point, with some damping, and this strategy has proved to be quite effective in practice. In this paper we present a statistical scheme that aims to improve that basic strategy by combining three individual methods together: simple persistence, canonical correlation analysis (CCA), and nearest‐neighbour regression. Several weighting schemes were tested: the best of these is one that uses equal weight in all areas except the east tropical Pacific, where CCA is preferred. The overall performance of the combined scheme is better than the individual schemes. The results show improvements in tropical ocean regions for lead times beyond 1 or 2 months, but the skill of simple persistence is difficult to beat in the extratropics at all lead times. Aspects such as averaging periods and grid size were also investigated: results showed little sensitivity to these factors. The combined statistical SST prediction scheme can also be used to improve statistical regional rainfall forecasts that use SST anomaly patterns as predictors. Copyright © Crown Copyright 2003. Published by John Wiley & Sons, Ltd.

Paleolimnology of Lake Tanganyika, East Africa, over the past 100 kyr - Christopher A. Scholz; John W. King; Geoffrey S. Ellis; Peter K. Swart; J. Curt Stager; Steven M. Colman (Journal of Paleolimnology, 2003)

Regulation of CD11b/CD18 (Mac-1) adhesion to fibrinogen by urokinase receptor (uPAR) - H. Zhang; R. W. Colman; N. Sheng (Inflammation Research, 2003)

STOIC: a study of coupled model climatology and variability in tropical ocean regions - Davey M.; Huddleston M.; Sperber K.; Braconnot P.; Bryan F.; Chen D.; Colman R.; Cooper C.; Cubasch U.; Delecluse P.; DeWitt D.; Fairhead L.; et al. (Climate Dynamics, 2002)

ENSIP: the El Niño simulation intercomparison project - M. Latif; K. Sperber; J. Arblaster; P. Braconnot; D. Chen; A. Colman; U. Cubasch; C. Cooper; P. Delecluse; D. Dewitt; L. Fairhead; G. Flato; et al. (Climate Dynamics, 2001)

Growth and tissue mass cycles in the infaunal bivalve Yoldia eightsi at Signy Island, Antarctica - L. S. Peck; J. G. Colman; A. W. A. Murray (Polar Biology, 2000)

Biogenic silica from the BDP93 drill site and adjacent areas of the Selenga Delta, Lake Baikal, Siberia - Steven M. Colman; John A. Peck; Josephine Hatton; Eugene B. Karabanov; John W. King (Journal of Paleolimnology, 1999)

Towards the prediction of the East Africa short rains based on sea-surface temperature–atmosphere coupling - C. C. Mutai; M. N. Ward; A. W. Colman (International Journal of Climatology, 1998)